2013
DOI: 10.1161/circep.113.000517
|View full text |Cite
|
Sign up to set email alerts
|

Novel Electromyographic Monitoring Technique for Prevention of Right Phrenic Nerve Palsy During Cryoballoon Ablation

Abstract: Background-Right phrenic nerve palsy (PNP) is the most frequent complication of cryoballoon ablation. Diaphragmatic electromyography can predict PNP with a comfortable safety margin. Our goal was to evaluate the feasibility, efficacy, and safety of electromyography-guided PN monitoring using a novel hepatic vein approach for prevention of PNP. Methods and Results-This study includes 57 patients (47 males) indicated for cryoballoon ablation for treatment of atrial fibrillation. During right superior pulmonary v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
48
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 10 publications
1
48
2
Order By: Relevance
“…8 More recently, we published a 57-patient series with the electromyography-guided PNM using a catheter placed in a hepatic vein during ablation with CB1. 5 The main advantage of hepatic vein placement is stable CMAP amplitude, despite respiratory movements. No PNP occurred but the cut-off value was reached in 6 patients requiring discontinuation of right superior pulmonary vein cryoapplication with forced deflation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 More recently, we published a 57-patient series with the electromyography-guided PNM using a catheter placed in a hepatic vein during ablation with CB1. 5 The main advantage of hepatic vein placement is stable CMAP amplitude, despite respiratory movements. No PNP occurred but the cut-off value was reached in 6 patients requiring discontinuation of right superior pulmonary vein cryoapplication with forced deflation.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] In a previous report, 5 we described a novel preventive technique involving real-time diaphragmatic electromyography using a recording catheter positioned in a subdiaphragmatic hepatic vein. If a 30% decrease in compound motor action potential (CMAP) amplitude was observed, cryoapplication was immediately discontinued with forced deflation to avoid PNP.…”
mentioning
confidence: 99%
“…9,10,17,18 Recently reported endoluminal esophageal temperature cutoffs have resulted in a significant reduction in thermal esophageal injury, whereas the development and evaluation of multiple safety algorithms to prevent phrenic nerve palsy, such as compound motoric activation potential pacing or the double-stop technique, have further improved the safety profile of the second-generation CB. 11,17,19,20 It had yet to be evaluated whether the greater clinical efficacy of the second-generation CB is because of a higher rate of permanently isolated PVs. Using the first-generation CB, the rate of electric reconduction was 54%.…”
Section: Discussionmentioning
confidence: 99%
“…The study by Guhl et al 40 systematically demonstrated an increased risk for phrenic nerve injury with the use of the 23-mm cryoballoon as well as with advanced age. The injury was transient for the majority of their cohort, and they noted that recommendations of monitoring diaphragmatic electromyographic signals with compound motor action potential [41][42][43][44][45] and rapid balloon deflation or double deflation leading to a more rapid tissue warming may reduce the extent of phrenic nerve injury. 46 The study by Mugnai et al 47 reported that the overall complication rate using second-generation cryoballoon PVI was 2%, with vascular access being a frequent major complication.…”
Section: S T Mathew and S S Pomentioning
confidence: 99%